Staining and aging-dependent changes in color of CAD-CAM materials - Stamenković, Dejan D.; Tango, Rubens Nisie [UNESP]; Todorović, Ana; Karasan, Duygu; Sailer, Irena; Paravina, Rade D. (Elsevier, 2020)
Statement of problem: Consumption of some beverages and aging may affect the color of dental materials used in fixed prosthodontics, but their effect on recently introduced materials is not well known. Purpose: The purpose of this in vitro study was to evaluate staining, aging, and the exposure interval on color changes of computer-aided design and computer-aided manufacturing (CAD-CAM) resin nanoceramics (RNC), polymer-infiltrated ceramic-network (PICN) materials, and lithium silicate and lithium disilicate ceramics. Material and methods: A total of 288 square-shaped, 1-mm-thick specimens prepared from Cerasmart, IPS e.max, Lava Ultimate, Shofu HC, Vita Enamic, and Vita Suprinity were polished by using laboratory and chairside methods in accordance with the manufacturers’ instructions. Color data were recorded with a benchtop spectrophotometer, and CIEDE2000 color differences (ΔE00) were calculated. After the baseline measurements (T0), the specimens were divided into 3 groups (n=8) and exposed to staining in coffee and wine and to accelerated artificial aging. The specimens were stored in staining solutions at 37 °C for 60 (T1) and 120 hours (T2). Accelerated aging was performed by using a xenon lamp weathering test chamber for a total exposure of 150 (T1) and 300 kJ/m2 (T2). The results were analyzed by using the t test, ANOVA, and the Tukey honestly significant difference test (α=.05). Color differences of ΔE00 ≤0.8 and ≤1.8 corresponding to the 50:50% perceptibility threshold and 50:50% acceptability threshold were used to interpret the results. Results: As color differences (ΔE00) between laboratory and chairside polishing were not statistically significant (T=-0.81, P=.418), only the results for chairside polished specimens were presented. Color differences for the T0-T1 comparisons ranged from 0.2 to 4.2, T0-T2 from 0.3 to 6.5, and T1-T2 from 0.1 to 2.3. ANOVA showed significance of factors and for interactions (P<.05). Lithium silicate–based and lithium disilicate–based ceramic materials were more color stable than RCN and PICN materials on exposure to coffee and red wine. Color changes greater than acceptability threshold after immersion in coffee were recorded for 3 (T0-T1), 4 (T0-T2), and 2 (T1-T2) materials. Corresponding findings after immersion in wine were 1, 3, and 0 and after artificial aging 0, 2, and 0. ΔE00 and ΔEab values were highly correlated (R2=0.97). Conclusions: No difference was found in color stability among laboratory and chairside polished specimens. Coffee caused the greatest color changes for T0-T2 interval. Staining-dependent color differences increased with increased exposure, except for IPS e.max and Vita Suprinity. For artificial aging, color change appeared to be material dependent.